2015
DOI: 10.1002/2015gl065298
|View full text |Cite
|
Sign up to set email alerts
|

The 2003–2004 seismic swarm in the western Corinth rift: Evidence for a multiscale pore pressure diffusion process along a permeable fault system

Abstract: Microseismic multiplets occurring in the western Corinth rift, Greece, during a large swarm are analyzed to retrieve their spatiotemporal characteristics. These multiplets activated small subfaults at depth (∼7 km), up to 1 km long, at the root of two parallel active normal faults. The swarm migrates westward nearly horizontally over 10 km at an average velocity of 50 m/d with a diffusivity of 0.5 m 2 s −1. It successively activates the Aigion fault, a relay zone in its hanging wall, and the Fassouleika fault.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 49 publications
7
63
0
2
Order By: Relevance
“…They accommodate the remote persistent creep at the root of the western detachment and the “mode I” extension by occasional ruptures. Note also that fluid overpressure could promote seismic ruptures, as proposed by Bourouis and Cornet [] and Duverger et al [] for multiplets active in 2003–2004.…”
Section: Discussionmentioning
confidence: 99%
“…They accommodate the remote persistent creep at the root of the western detachment and the “mode I” extension by occasional ruptures. Note also that fluid overpressure could promote seismic ruptures, as proposed by Bourouis and Cornet [] and Duverger et al [] for multiplets active in 2003–2004.…”
Section: Discussionmentioning
confidence: 99%
“…Fluids are also suspected to be a driving factor for seismic swarms (Cappa, Rutqvist, & Yamamoto, ; Hainzl, ; Hainzl et al, ; Leclère et al, ; Shelly et al, ). For example, seismic swarms observed in the Gulf of Corinth (Greece) are related to the diffusion of fluid overpressures (Duverger et al, ; Pacchiani & Lyon‐Caen, ). Moreover, observations indicated that even strong rainfalls can be a driver of seismicity (Hainzl et al, ; Miller, ; Rigo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The 2001 Agios Ioannis earthquake swarm took place in the southern part of the study area and was attributed to fluid-driven seismicity (Pacchiani & Lyon-Caen 2010). The next two seismic crises were originated offshore in 2003-2004 and 2006-2007, and for the first one evidence is provided that was related to fluid diffusion process (Bourouis & Cornet 2009;Duverger et al 2015). On 2007 April 08, the Trichonida earthquake swarm initiated near the area where the 1975 M = 6.0 earthquake occurred (Evangelidis et al 2008;Kiratzi et al 2008;Kassaras et al 2014).…”
Section: Introductionmentioning
confidence: 99%